UJI EKSPERIMENTAL MESIN PENDINGIN BERPENDINGIN AIR DENGAN MENGGUNAKAN REFRIGERAN R22 DAN REFRIGERAN R407C - Terry Gunawan; Harto Tanujaya; Asrul Aziz (Program Studi Teknik Mesin Universitas Tarumanagara, 2014)
Abstract: The human needs of refrigeration system have created a tool that called a refrigerator. Refrigerator/cooling machine have a component which have a very important role in the refrigeration system that is refrigerant. Refrigerant that still widely used for cooling machine until now is the refrigerant R22. Using R22 refrigerant can cause environmental problems such as damage to the ozone layer and global warming. Therefore, it needs a substitution refrigerant which is more friendly for environment which one of them is R407C refrigerant. In this study, using a cooling machine with water- cooled condenser and the flowrate that use is 20 L/h, 40 L/h, 80 L/h and 120 L/h. The variables that measured in this study is temperature (T1, T2, T3, T4, T10, T11), pressure (P1, P2, P3, P4), and ampere. This study aims to get the test results using refrigerants R22 and R407C. The processing data of the test result include refrigeration capacity, compressor power and COP. The results obtained have that cooling machine which use R22 refrigerants have a better COP than using R407C refrigerant. This is happen because the power needed by the compressor to compress R407C refrigerant to flow in the system is greater than using R22 refrigerant.